The Design and Construction of a Polyethylene Terephthalate Shredding Machine (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
Due to their non-biodegradable nature and insufficient disposal techniques, the extensive usage of polyethylene terephthalate (PET) plastics has raised serious environmental pollution concerns. This research project aims to design and develop an eco-friendly PET plastic shredding machine with improved performance, lower energy consumption, and less maintenance needs to address these problems. It incorporates enhanced blade structure, portability, and lower energy consumption, with major components designed using standard equations. Engineering drawings were created using SOLIDWORKS and analyzed on ANSYS before construction and testing. A dual hexagonal shaft with 32 242mm diameter shredder blades was designed, supported by a 1.5HP, 3-phase gear motor. The PET plastic shredder, measuring 928mmx350mmx817mm, underwent Finite Element Analysis with a 225Nm torque applied to the blade tip, resulting in a shear stress of 51.7Mpa, and a pressure equal to the plastic to be shredded. The main frame was tested for stress on the motor and shredding unit using a 6mm mesh size. To test, 10 PET plastic bottles weighing 310g each were fed into the hopper and shredded based on the volume of the hopper. A throughput of 3.1kg was obtained in 36.23s after shredding. Beyond the goals of waste reduction, issues regarding the economic and environmental impact of this machine were addressed and recommendations for improvement and further research were considered.